Environmental Impact Assessment of a School Building in Iceland Using LCA - Emami, Nargessadat, 1987- (2016)
Buildings play a key role in our lives and society as a complex system. Iceland provides an interesting case since the energy demand in the whole country is mostly supplied by geothermal and hydroelectric resources. Life cycle assessment, or LCA, has become an accepted tool to performing sustainability assessment of various systems including buildings. Therefore it was decided to apply it to develop a framework that enables us to make estimates of the environmental impacts of the materials used in the structure and envelope of the Vættaskóli-Engi building in Reykjavik, Iceland, during four modules of raw material extraction (A1), transportation to manufacturing site (A2), manufacturing of construction materials (A3) and transportation to the construction site (A4), as defined in the standard EN 15804. The environmental impacts covered in this study include global warming potential (GWP), Ozone depletion potential (ODP), Human Toxicity (HT), Acidification (AP) and Eutrophication (EP). It should be emphasized that, the construction work, use stage and end of life were excluded from this analysis. The overall environmental impacts of the Vættaskóli-Engi building from modules A1-A4 in terms of GWP, ODP, HT, AP and EP are estimated to be 1490 ton CO2 eq, 0.0305 kg CFC 11 eq, 0.262 CTUh, 5.5 kmol of H+ eq, 13 kmol of N eq, respectively; while per one square meter impacts are equal to 298 kgCO2/sqm, 6.11E-06 kg CFC 11 eq/sqm, 5.22E-05 CTUh/sqm, 1.10 Mole of H+ eq/sqm and 2.56 Mole of N eq/sqm. As expected concrete, aluminum windows and reinforcing steel represent 70%-85% of total environmental impacts. Based on the developed model in GaBi, it was found that 1 kg of stone wool produced in Iceland emits between 59-67% less CO2 compared to the similar processes in UK and Germany. The results of this analysis confirms the suitability of using life cycle analysis approach to assess the environmental impacts of construction materials. The outcomes enabled us to make comparisons with similar studies in other countries and ...